Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1149/1945-7111/ab6bc2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electrolyte Additives upon Lithium Plating during Low Temperature Charging of Graphite-LiNiCoAlO2 Lithium-Ion Three Electrode Cells

Abstract: The effects of lithium-ion electrolyte additives in ester-rich low temperature electrolyte blends, including vinylene carbonate (VC), lithiuma bis(oxalato) borate (LiBOB), lithium difluoro(oxalato)borate (LiDFOB), propane sultone (PS) and lithium bis(fluorosulfonyl)imide (LiFSI), upon the likelihood of lithium plating are investigated in graphite-LiNiCoAlO2 three-electrode cells. Although metallic lithium is generally absent in lithium-ion cells, certain conditions, particularly charging at low temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…Jones et al. [ 68 ] further examined the polarization resistance on the cathode with different types of Li salts additives. The electrolyte with LiBOB additive produced the lowest polarization resistance at −40 °C (2.42 Ω), indicating the best charge transfer kinetics.…”
Section: Strategies For Low Temperature Electrolyte Designmentioning
confidence: 99%
“…Jones et al. [ 68 ] further examined the polarization resistance on the cathode with different types of Li salts additives. The electrolyte with LiBOB additive produced the lowest polarization resistance at −40 °C (2.42 Ω), indicating the best charge transfer kinetics.…”
Section: Strategies For Low Temperature Electrolyte Designmentioning
confidence: 99%
“…Abe et al [228]showed that in two types of preformed SEI at the interface of HOPG-Electrolyte (1M LiClO4 in 1:1 EC:DEC), the activation energy for the charge transfer through the SEI formed with Pentafluorostyrene (PFS) additive was 40 kJ/mol compared to 52 kJ/mol for SEI formed without the additive. Various other experiments [228,233] supported that changing SEI/CEI composition through electrolyte additives 1 exp( )…”
Section: Kinetic Lossesmentioning
confidence: 84%
“…The most common recent development, however, has seen ester-based formulations paired with interface-modifying additives, including VC, 91,102-104 FEC 103,105 and others. 74,104 For instance, Jones et al tested a series of additives for their ability to inhibit lithium plating during low-temperature charge in a MP-rich electrolyte, finding 0.1 M LiFSI to be most effective. 104 In at least one case, additives have made it possible to eliminate EC from the electrolyte entirely, with a MP : VC 95 : 5 w/w electrolyte allowing acceptable capacity retention during 40 1C cycling of Gr8NMC 111 pouch cells and enabling significantly-improved rate performance at À14 1C compared to an EC/EMC/VC mixture.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%